Study on Corrosion Resistant Materials for Centrifugal Pump Impeller - R. Navaneetha; Ch. Indira Priyadarsini; T. Ratna Reddy (Research Developments in Science and Technology Vol. 5, 2022)
An impeller is a revolving component that increases or lowers fluid flow and pressure and has a wide range of applications in the aircraft, automobile, medical, and power plant industries. When exposed to damaging mediums such as waste water, seawater, sewage, chlorine, bromine, and a variety of chemicals in real-time applications, bronze and hardened steel impellers swiftly degrade. They are reliant on cavitations and electrolysis (galvanic erosion), which rapidly degrade the impeller. Corrosion is a key issue with impellers, which drives up pump operating and maintenance costs, forcing industry to look for alternate materials. The major objectives of this work is to choose the best material for the impeller that will resist corrosion. Materials such as Caprolone (Nylon) and ABS (Acrylonitrile Butadiene Styrene) have been consider for the study than conventional materials like stainless steel and bronze. The simulation results have shown that the ABS material performed well in terms of corrosion resistance as it has chemical, thermal stability along with toughness and strength.